Analiza Rządowego Programu Współpracy z Polonią i Polakami za Granicą na lata 2015-2020 w zakresie polityki edukacyjnej Rządu RP w stosunku do polskiej mniejszości narodowej na Ukrainie - Staszkiewicz, Anita (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The analysis of the Governmental Program for Cooperation with the Polish Diaspora for the years 2015-2020 in scope of education policy of the Polish Government towards the Polish national minority in Ukraine. The paper refers to the analysis of of the Governmental Program for Cooperation with the Polish Diaspora for the years 2015-2020 in scope of education policy of the Polish Government towards the Polish national minority in Ukraine. This program was accepted by the government and it is a kind of purpose for beginning a dialog with a very diferenciated (from the point of view of social positions, political situation in the country, level of knowledge of the Polish language and identifying theirselves with Poland) group of the Polish diaspora and Poles living abroad. It is also an attempt to meet very differentiated needs of this community. Ukraine is a multinational country. Social position of the Polish national minority is comparable to economic and social situation of the other minorities. The Poles in Ukraine are treated as a national minority. The Polish national minority is in general elegible to cultural and national autonomy that is guaranteed by the law and excersises this right first of all by setting up cultural societies aiming to teach the Polish language, popularization of Polish culture and developing folk traditions. The strategic goals of the Governmental Program are: giving suport to teaching the Polish language, studies about Poland conducted in Polish, strengthening Polish identity and ensuring participation in Polish cultural life, consolidation of Polish communities abroad, giving suport to their return to Poland, encouraging people of Polish origin to settle themselves in Poland and multilevel development of their contacts with Poland. We can identify these goals in the following order: - improving the quality of the institutions infrastructure starting from their renovetion and repair, equiping them with stationery, methodological guidances and educational materials; - financial suport for extracurricular education (lessons in libraries, educational excursions, special activity groups); - strengthening motivation system in studying the Polish language for children who are ofthen forced to study foreign languages by their parents; - imrovement of the Polish language teachers qualifications by organizing specific cources and seminars both in Poland and Ukraine; - encouraging the young generation of the teachers to practice their profession as the teachers of the Polish language by creating a system of additional remunerations and increasing the prestige of this profession; - improvement of managing teams qualifications by organizing training activities and cources that meet the needs of these specific institutions; - enrichment of the grants range for pupils of all the levels of school education; - involvement of parents in the proces of education by their participation in educatinal performances. The Program assumptions are undoubtedly relevant to the needs of the educational system units. Considering increasing interest in learning the Polish language, the range of suport is the thing that remains a challenge while identyfying its forms is much more easy.